Capital Structure , Green Accounting dan Firm Debt: Implikasinya terhadap Financial Performance - Oktavianna, Rakhmawati; Saputri, Sevty Wahiddirani; Benarda, Benarda (Jurnal Liabilitas, 2025)
This study examines and analyzes the impact of capital structure, green accounting, and corporate debt on the financial performance of industrial companies. This study uses panel data consisting of 54 samples from 2018 to 2023. The research findings indicate that capital structure and corporate debt affect financial performance. When debt levels are high, it can reduce financial performance, because high debt levels may result in higher capital costs due to interest payments. However, green accounting does not affect financial performance because environmental costs incurred by companies can reduce a company's profits due to its use for environmentally friendly production tools, conservation, and environmental maintenance. This study contributes to companies achieving good financial performance by using less debt funding, because the risk of disclosing debt securities has a high risk, such as the possibility of financial difficulties due to the inability to pay high interest.